Rancang Bangun Sistem Informasi Berbasis Website Pada Desa Tonrong Tengnga Kabupaten Wajo - Fadli, Zul; Amriadi; Muliana (Jurnal Bisnis Digital dan Enterpreneur (BISENTER), 2023)
Website-based information systems have become a popular solution to provide fast and easy access to information for users. Tonrong Tengnga Village is a village that has tourism potential and superior products that need to be promoted through information technology. This study aims to design and develop a website-based information system for Tonrong Tengnga Village. The method used in this research involves needs analysis, system design, implementation, and evaluation. The result of this research is a website-based information system that is able to provide information about tourism potential, superior products, event agendas, and the latest news from Tonrong Tengnga Village. This system is equipped with search features, location maps, and a contact form to make it easier for users to interact with village officials. System evaluation is carried out by soliciting input from users, which shows that this information system is effective and efficient in providing access to information about Tonrong Tengnga Village.